PERAN DYNAMIC CAPABILITY DALAM MENGOPTIMALKAN ANALISIS COST VOLUME PROFIT (CVP) SEBAGAI ALAT PERENCANAAN LABA PADA UMKM BUBUR AYAM DAN AYAM GEPREK BU ARNIZ - Hanum, Fadia Agustina; Fahriani, Dian (LPPM Universitas Putera Batam, 2025)
This study aims to analyze the influence of competence, discipline, and pain The reserch aims to analyze the financial potential and performance of the UMKM Bubur Ayam and Ayam Geprek Bu Arniz in 2024, using Cost Volume Profit (CVP) analysis to plan for more effective profits. In the face of increasingly intense competition, it is crucial for businesses to develop dynamic capabilities and appropriate strategies. This research uses a qualitative approach with a field study, involving the UMKM owner as the main informant, to understand the internal and external conditions and how the business adapts to environmental changes. The results show that the business has significant financial potential, with sales reaching IDR 284,700,000. The break-even point is achieved at 412 servings or IDR 5,373,913 in revenue, with a contribution margin ratio of 69%, meaning nearly 70% of sales are used to cover fixed costs and generate profits. The Margin of Safety of IDR 279,326,087 indicates room for a decrease in sales without incurring losses, while the Degree of Operating Leverage of 1.01 shows a small impact of sales changes on profit. Overall, Bubur Ayam and Ayam Geprek Bu Arniz demonstrates positive performance and has the potential for continued growth, particularly with product innovation and a strong understanding of market needs.